2008
DOI: 10.1007/s11250-008-9152-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydatidosis of slaughtered animals in Bahir Dar Abattoir, Northwestern Ethiopia

Abstract: The study was conducted from May 2005 to December 2006 in Bahir Dar Abattoir to assess the current status of hydatidosis in cattle and sheep. Hydatid cyst count and characterization were conducted based on routine meat inspection. Of the total 420 cattle and 340 sheep slaughtered in Bahir Dar Abattoir 143 (34.05%) and 36 (10.6%) animals were found harboring hydatid cysts respectively. Thorough meat inspection in the abattoir revealed that 202 and 54 visceral organs were found harboring one or more hydatid cyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
57
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 13 publications
18
57
7
Order By: Relevance
“…This finding is in agreement with previous study by Yilma Jobre et al, (1996) and Nigatu Kebede et al, (2009c). The difference in infection rates between different species of animals might be explained mainly as a result of the involvement of different strains of E. granulosus, variations in feeding behaviors of the animals and animal husbandry practices.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is in agreement with previous study by Yilma Jobre et al, (1996) and Nigatu Kebede et al, (2009c). The difference in infection rates between different species of animals might be explained mainly as a result of the involvement of different strains of E. granulosus, variations in feeding behaviors of the animals and animal husbandry practices.…”
Section: Discussionsupporting
confidence: 93%
“…In Assela, where there are multiple records, higher prevalence of bovine and ovine hydatidosis was observed in the most recent report than in the older ones. The mean prevalence value reported in the present work concords with the recently reported prevalence of 34.05% in cattle and 10.6% in sheep from Bahir Dar (Nigatu Kebede et al, 2009c), 32.11% in cattle from Mekelle (Gebretsadik Berhe et al, 2010) and 29.69% in cattle from Ambo (Endrias Zewdu et al, 2010). Slightly higher prevalence of 48.9% in cattle from Debre Markos (Kebede Nigatu, et al, 2009a), 46.8% in cattle, 29.3% in sheep, and 6.7% in goats from Nazareth (Getaw et al, 2010) and 52.69% in cattle from Hawassa (Feyessa Regassa et al, 2010) were also reported.…”
Section: Discussionsupporting
confidence: 83%
“…In agreement with our findings [31], in northwestern Ethiopia, reported the sterile cysts as the most prevalent type of removed hydatid cysts [31,32], Additional [32], in Arak province of Iran, found calcified cysts as the least type among all hydatid cysts [31], however opposite to our finding, in Sardinia (Italy) calcified cysts were observed as the most prevalent [33]. In our statistical analysis showed a significant relation of cysts, fertility and their size.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is lower than the reports from other places in Tanzania and neighboring countries with 4.2% in Arusha [23] , 47% in Ngorongoro [10] and 31% in South West Ethiopia [24] . Factors such as differences in culture, social activity, animal husbandry systems, lack of proper removal of infectious carcases, abundance of infective definitive host and attitude to dogs in different regions might have contributed to the variation in prevalence in different areas of a country [25,26] . The rates of infection between breeds showed that local breeds were found to harbor a significantly higher infection than graded or crossbred.…”
Section: Discussionmentioning
confidence: 99%